Application of structural equation modelling to analyse the impacts of logistics services on risk perception, agility and customer service level - Avelar, Liliana (2018)
Logistics services of manufacturing enterprises help to improve transport, delivery of materials and finished products. This paper presents a causal model to identify the influence that has the availability of logistics services on the risk perception, on agility and on customer service level of manufacturing companies. A questionnaire was developed, validated and applied to 225 employees of different industrial sectors. Information is integrated in a structural equation model for test seven hypotheses using partial least squares to calculate the regression coefficient between variables using 95 % confidence level. The results mainly indicated that the availability of logistics services have a positive and direct effect on risk in demand and in supplier's risk; but in addition, agility and transportation also have effects over them. All these variables have direct or indirect contributions on customer service level and can explain 45 % of its variability